2007
DOI: 10.1007/s11274-007-9357-z
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic fungi from Nerium oleander L (Apocynaceae): main constituents and antioxidant activity

Abstract: Diverse endophytic fungi exist within plant aerial tissues, with a global estimate of up to a million undescribed species. These endophytes constitute a rich bio-resource for exploration to discover new natural products. Here we investigate fungal endophytes associated with a medicinal plant, Nerium oleander L. (Apocynaceae). A total of 42 endophytic fungal strains were isolated from the host plant. Total antioxidant capacity, xanthine oxidase inhibitory activity, antimicrobial activity, and total phenolic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
61
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(73 citation statements)
references
References 42 publications
8
61
2
2
Order By: Relevance
“…Strobel et al (2002) & Harper et al (2003 obtained two antioxidants, pestacin and isopestacin, from the endophytic fungus Pestalotiopsis microspora. The endophytic fungi residing in Nerium oleander were shown to have excellent antioxidant capacity and preliminary identification detected phenolics and volatile and aliphatic compounds by Huang et al (2007). The results of this study are similar to those in previous reports and indicate that endophytic fungi may serve as a potential source of antioxidants.…”
Section: Discussionsupporting
confidence: 89%
“…Strobel et al (2002) & Harper et al (2003 obtained two antioxidants, pestacin and isopestacin, from the endophytic fungus Pestalotiopsis microspora. The endophytic fungi residing in Nerium oleander were shown to have excellent antioxidant capacity and preliminary identification detected phenolics and volatile and aliphatic compounds by Huang et al (2007). The results of this study are similar to those in previous reports and indicate that endophytic fungi may serve as a potential source of antioxidants.…”
Section: Discussionsupporting
confidence: 89%
“…Hence, an appreciable amount of flavonoids produced by the endophytic fungi may be present in the quantity verified in the plant; moreover, they contributed to its synthesis. Huang et al (2007) isolated 42 endophytic fungi from Nerium oleander and found flavonoids among the main bioactive compounds of some cultures. They also clarified that some phenolic compounds are produced so that certain endophytic fungi survive along with their host plants.…”
Section: Discussionmentioning
confidence: 99%
“…Most endophytes are capable of synthesizing bioactive compounds that may provide plants with a defense against pathogens, and some of these compounds have proven useful for novel drug discovery (Guo et al, 2008;Yan et al, 2011). Since the chemical constituents from medicinal plants were complex, more and more endophytic fungi with novel metabolites of pharmaceutical importance were isolated from medicinal plants, and a series of new and useful compounds were obtained (Huang et al, 2007;Guo et al, 2008;Kusari et al, 2009). No doubt, exploiting a variety of new natural products from endophytic fungi of medicinal plants has become a hot spot of new drug research.…”
Section: Introductionmentioning
confidence: 99%